1973
DOI: 10.1079/bjn19730036
|View full text |Cite
|
Sign up to set email alerts
|

Rate of passage of digesta in sheep

Abstract: 1. The rates of passage of markers of fluid and particulate digesta through the sheep alimentary tract have been described mathematically in single-injection experiments by analysing the concentration curves of marker excretion in faecal dry matter and then predicting these concentrations by means of an equation containing two exponential terms. Three components related to this equation are a transit time for digesta in the intestines, a half-time of marker in the reticulo-rumen and a half-time tentatively ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
47
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(54 citation statements)
references
References 38 publications
7
47
0
Order By: Relevance
“…The 144 Ce/ 144 Pr system has found application as a radiotracer in nutritional science more than 30 years ago, where the elimination of the Ln-EDTA complex in sheep was found to be more rapid than the corresponding 51 Cr system. 82 The complex 51 Cr-EDTA was excreted faster in faeces than 144 Ce/ 144 Pr when both were given together as a single injection into the reticulorumen. In fundamental studies, Sherry and co-workers previously reported the thermodynamic properties of Ln(III) complexes of common triaza and tetraaza macrocycles, including EDTA, NOTA, DTPA and DOTA (Fig.…”
Section: Macrocyclic Ligand Derivativesmentioning
confidence: 99%
“…The 144 Ce/ 144 Pr system has found application as a radiotracer in nutritional science more than 30 years ago, where the elimination of the Ln-EDTA complex in sheep was found to be more rapid than the corresponding 51 Cr system. 82 The complex 51 Cr-EDTA was excreted faster in faeces than 144 Ce/ 144 Pr when both were given together as a single injection into the reticulorumen. In fundamental studies, Sherry and co-workers previously reported the thermodynamic properties of Ln(III) complexes of common triaza and tetraaza macrocycles, including EDTA, NOTA, DTPA and DOTA (Fig.…”
Section: Macrocyclic Ligand Derivativesmentioning
confidence: 99%
“…Marker passage studies showed that on maize cob leaves a significant part of the flow pattern, normally associated with mixing in the hindgut, originated anterior to the ileum while on lucerne it did not show the same pattern.Key words: Sheep, digesta, mixing compartments, marker passage Digesta flow kinetics in the whole digestive tract was first described by Blaxter et al (1956) and later substantiated by Grovum and Williams (1973) For personal use only. …”
mentioning
confidence: 99%
“…Key words: Sheep, digesta, mixing compartments, marker passage Digesta flow kinetics in the whole digestive tract was first described by Blaxter et al (1956) and later substantiated by Grovum and Williams (1973) For personal use only.…”
mentioning
confidence: 99%
“…Summary ― Seventy nine fecal excretion curves of rare earth were adjusted with 3 published models (Grovum and Williams, 1973;Ohanoa et al, 1985;Siddons et al, 1983 …”
mentioning
confidence: 99%
“…
Summary ― Seventy nine fecal excretion curves of rare earth were adjusted with 3 published models (Grovum and Williams, 1973; Ohanoa et al, 1985;Siddons et al, 1983). The models provided statistically similar estimations of particulate tumover in the first compartment and mean retention time.
…”
mentioning
confidence: 99%